Impact of ageing population towards pension expenditure in Malaysia: an ARDL approach / Nurul Dahiyah Shahirah Alias and Rose Irnawaty Ibrahim - Alias, Nurul Dahiyah Shahirah; Ibrahim, Rose Irnawaty (Universiti Teknologi MARA, 2025)
When the aging population increases, the demand for pension is also higher causing pension expenditure to also increase. Persistent increase in pensions expenditure can cause strain on government budgets and pose sustainability challenges for pension systems in the future. Therefore, this empirical study delves into the relationship between population aging and pension expenditure and identifies both short-term and long-term relationships between pension expenditure and its determinant for the sample spanning from 1970 to 2020. This study uses Autoregressive Distributed Lag (ARDL) model to achieve the objectives. The independent variables are life expectancy, the population aged 65 and above, total fertility rate and growth domestic products (GDP) per capita. The findings indicate that the population ages 65 and above has the most significant impact on pension expenditure in the short run and long run. In addition, the findings also propose that there are both short run and long run relationships between life expectancy, total fertility rate, the population aged 65 and above, and GDP per capita with pension expenditure in Malaysia. Above all, this research intends to contribute valuable findings for policymakers and the government in making crucial decisions.